Seed Germination and Early Seedling Growth of Wheat (Triticum aestivum Linn.) cv. 1553 Under the Influence of Salinity and Plant-growth Hormones - Babu, V Ramesh; Kumar, Sunil (Annals of Arid Zone, 2016)
Plant hormones-benzyl adenine' and kinetin were found effective in promoting seed germination and seedling survival under osmotically stressed conditions by soil salt ;solutions upto 3.5 percent. The two hormones had corrective influence in seedling dry miller mobilizltion upto 1.5 percent soil solution. Water content of seedlings was also found to increase under hormonal influence, while seedlings beyond I 0 percent showed reduced water content in controls. Similar differences were observed in the root and shoot elongation.